Plumbagin: A Potential Anti-cancer Compound - Roy, Arpita (Mini Reviews in Medicinal Chemistry, 2021)
Cancer is a deadly disease, which has significantly increased in both developed and developing nations. Treatment of cancer utilizing radiotherapy or chemotherapy actuates a few issues which incorporate spewing, sickness, unpalatable reactions, and so forth. In this specific situation, an alternative drug source, which can effectively treat cancer is of prime importance. Products that are obtained from plant sources are utilized for the treatment of various diseases due to their non-harmful nature. Medicinal plants contain different bioactive compounds, which possess an important role in the prevention of different diseases such as cancer. Plumbagin is a bioactive compound, which is mainly present in Plumbaginaceae family and has been explored for its anticancer activity. Plumbagin basically inactivates the Akt/NF-kB, MMP-9 and VEGF pathways that are essential for cancer cell development. Therefore, it is important to review the role of plumbagin in different cancer cells in order to find an alternative drug to overcome this disease. The present review provides a summary of anticancer activity of plumbagin in various cancers and its mode of action.
Keywords: lung cancer